ANALYSIS OF THE IMPACT OF E-CRM IN INCREASING CUSTOMER SATISFACTION AND LOYALTY TO THE INDONESIAN MARKETPLACE - Miftahul Husna Hutapea; Liska Febrianti; Nurbaiti Nurbaiti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
With the development of the times, technology has also developed. One example is entrepreneurs who run their business through online. With this in building and maintaining good relationships with customers, entrepreneurs really need technology. Until now, there are many types of marketplaces in Indonesia, but there are three types of marketplaces that survive and compete with each other, including Tokopedia, Shopee and Bukalapak. Tokopedia is one of the online companies that implements E-CRM in maintaining and building good relationships for the company's customers. PT Tokopedia Indonesia besides having an online buying and selling website, this company also has an online sales application which is one of the marketplace companies in Indonesia. In this study, we used a descriptive qualitative method where we collected data using several journals and also the official website to get the data we needed, such as data on the level of how often customers make transactions and also Tokopedia customer satisfaction level data. Then we will analyze this data to determine the level of loyalty and customer satisfaction on the official application and website of the Tokopedia company.